2003
DOI: 10.1034/j.1600-0528.2003.00016.x
|View full text |Cite
|
Sign up to set email alerts
|

Time and duration of eruption of first and second permanent molars: a longitudinal investigation

Abstract: A tremendous variation was found in time of eruption and in duration of eruption of permanent molars. This variation highlights the importance of individualizing caries preventive strategies for children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1
23

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 11 publications
5
50
1
23
Order By: Relevance
“…18 Some authors have asserted that the first permanent molars are more susceptible to develop caries lesions during the eruption period. 4,8,14 It was observed that partially erupted first permanent molars had more abundant visible plaque and a greater proportion of active caries lesions than fully erupted ones. 4 However, in the present study, there was no significant association between eruption degree of the first permanent molars and the presence of active caries lesions in these teeth.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…18 Some authors have asserted that the first permanent molars are more susceptible to develop caries lesions during the eruption period. 4,8,14 It was observed that partially erupted first permanent molars had more abundant visible plaque and a greater proportion of active caries lesions than fully erupted ones. 4 However, in the present study, there was no significant association between eruption degree of the first permanent molars and the presence of active caries lesions in these teeth.…”
Section: Discussionmentioning
confidence: 98%
“…Quarenta e oito crianças (5,(8)(9)(10)(11)(12)(13)8 anos) com pelo menos um primeiro molar permanente foram selecionadas. Os parâmetros clínicos avaliados foram sexo, idade, CPO-D e ceo-d, presença de manchas brancas ativas em outros dentes, índice de placa, arco dentário do dente (superior ou inferior), lado do dente (direito ou esquerdo), presença de placa visível e grau de erupção dos primeiros molares permanentes.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The study had a longitudinal prospective design with a cohort of subjects of whom many had periodontal disease documented at baseline 16 Further comments should be made about the missing molars which in this study were used as a proxy for chronic dental infections. The first permanent teeth to erupt are the first and second permanent molars [32]. The newly erupted molars can be infected by oral bacteria from the primary dentition or by intra-familial transmission [33][34].…”
Section: Discussionmentioning
confidence: 99%
“…1 Tooth eruption is still a guide to a child's age both in social and clinical contexts. 2 Recently, tooth devel opment data from radiographs have been used in the estimation of the biological age of children adopted from overseas where there is unreliable, or nonexistent documentation of the birth date. In addition, an increasingly common request is to assess the age of young asylum seekers deemed to be over 18 years of age by the Immigration Bureau of the United Kingdom.…”
Section: Introduction Backgroundmentioning
confidence: 99%